1992
DOI: 10.1073/pnas.89.12.5586
|View full text |Cite
|
Sign up to set email alerts
|

cAMP-mediated differential regulation of lignin peroxidase and manganese-dependent peroxidase production in the white-rot basidiomycete Phanerochaete chrysosporium.

Abstract: Lignin peroxidases (LIPs) and manganesedependent peroxidases (MNPs) are major components of the -ignin-degrading enzyme system of Phanerochaete chrysosporium and typically appear during secondary metabolism. The involvement of cAMP in the regulation of production of LIPs and MNPs was investigated in this study. Production of LIPs and MNPs was preceded by a sharp rise in intracellular cAMP concentration. Addition of atropine, theophylline, or histamine to cultures resulted in a drop in intracellular cAMP concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 40 publications
1
42
0
Order By: Relevance
“…Boominathan and Reddy (7) suggested that transcription from genes encoding certain LIP enzymes is controlled by cAMP levels, a starvation signal. We found that intracellular cAMP levels responded to starvation conditions and that similar cAMP levels occurred with or without oxygenation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Boominathan and Reddy (7) suggested that transcription from genes encoding certain LIP enzymes is controlled by cAMP levels, a starvation signal. We found that intracellular cAMP levels responded to starvation conditions and that similar cAMP levels occurred with or without oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…Liquid cultures of P. chrysosporium must be starved (nitrogen or carbon depletion) and exposed to a pure O 2 atmosphere to trigger LIP expression (4,11,26). Boominathan and Reddy (7) showed that transcription of genes encoding some LIP enzymes is controlled by cyclic AMP (cAMP) levels.…”
mentioning
confidence: 99%
“…(1990) showed that this enzyme was detectable only in cells grown in the presence of MO and that its induction was blocked in the presence of transcriptional inhibitors, suggesting a role for Mn2+ as a transcriptional regulator as well as a substrate. The regulation of MnP and lignin peroxidase is believed to be mediated by cAMP since changes in intracellular levels of this compound resulted in the differential regulation of these two enzymes (Boominathan and Reddy, 1992). The lack of LiP activity in cultures with high concentrations of Me' could be due to increased levels of phosphodiesterase, which degrades cAMP and is stimulated by Mn2+.…”
Section: Control Effects By Environmental Factorsmentioning
confidence: 99%
“…Fax: +81-24-593-2155; E-mail: yamagisi@affrc.go.jp Abbreviations: RAS, Schizophyllum RAS gene; ScGP-A, Schizophyllum commune G protein alpha subunit A; ScGP-C, Schizophyllum commune G protein alpha subunit C and bioremediation. [13][14][15] Although the mechanism regulating the cAMP level in homobasidiomycete has not yet been explained, the putative components that are supposed to activate adenylyl cyclase have been reported. The homobasidiomycete RAS gene was first identified from Lentinus edodes (LeRas), which could functionally replace its homolog genes (ScRAS1 and ScRAS2) in S. cerevisiae.…”
mentioning
confidence: 99%